APPLYING AHP FOR THE DETECTION OF THE BRIDGE CONDITION IN KUDUS - Setiaji, Pratomo; Setiawan, Arif (Proceedings of KNASTIK, 2012)
The Storing methods which use paper, so far brings the Dinas Pekerjaan Umum ofKudus regency to the problems of determining the bridge destructions priority dueto the fact that unintegrated data, and there are no detail statistical information's.One of the methods that could integrate technical aspect of the location selectionsefficiently and accurately is AHP (Analytic Hierarchy Process)Research uses statistical method by using AHP since it is able to simplify thecomplicated material. Therefore, the hierarchy method of decision making would beefficiently. In addition, it shows a comparison grade of each criteria to determinethe value, bridge detector designed by using AHP method used by DPU of Kudusregency to rank the bridge condition.